A current-observer-based induction motor speed sensorless control and use of DC link current - Mineo Tsuji; Fujin Xu; Tsuruda, J.; Hamasaki, S.; Yamada, E. (2012 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2012)
We have proposed a current observer-based speed sensorless vector control system which is composed in a rotating reference frame. The characteristic improvement of this system is discussed by taking into account observer gain. The stability of the system has been investigated by the trajectories of poles and zeros. The effectiveness of the proposed system has been investigated by experimentation. Furthermore, a speed sensorless system in which a DC link current sensor is only used without phase currents sensors is proposed and discussed.